2015
DOI: 10.1080/10426507.2015.1024312
|View full text |Cite
|
Sign up to set email alerts
|

Selenophene as a Bridge in Molecular Architecture of Benzotriazole Containing Conjugated Copolymers to Gain Insight on Optical and Electrochemical Properties of Polymers

Abstract: Polymers containing selenophene as a π bridge; poly(2-(2-octyldodecyl)-4-(selenophen-2-yl)-7-(5-(thiophen-2-yl)selenophen-2-yl)-2H-benzo[d][1,2,3]triazole) (P1) and poly(2-(2-Downloaded by [FU Berlin] at 18:45 25 June 2015 ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 2 octyldodecyl)-4-(5-phenylselenophen-2-yl)-7-(selenophen-2-yl)-2H-benzo[d][1,2,3]triazole (P2) were synthesized via Stille and Suzuki coupling reactions respectively. Optical and electrochemical properties were investigated and comparisons with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…The monomer 1 was polymerized and characterized in 0.1 M TBAH dissolved CH 2 Cl 2 . After polymerization and before characterization, the corresponding polymer P1 coating on the working electrode surface was washed with CH 2 Cl 2 , and to break in the polymer film, its redox state was switched a number of times 32 and tributyl(selenophen-2-yl)stannane 16 were carried out according to accepted procedures found in the literature. The spectral data were well in agreement with those reported previously for these compounds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monomer 1 was polymerized and characterized in 0.1 M TBAH dissolved CH 2 Cl 2 . After polymerization and before characterization, the corresponding polymer P1 coating on the working electrode surface was washed with CH 2 Cl 2 , and to break in the polymer film, its redox state was switched a number of times 32 and tributyl(selenophen-2-yl)stannane 16 were carried out according to accepted procedures found in the literature. The spectral data were well in agreement with those reported previously for these compounds.…”
Section: Methodsmentioning
confidence: 99%
“…There have been few studies on D-A-D based polyselenophenes. 7,[14][15][16] 2,1,3-Benzothiadiazole [17][18][19][20][21] and quinoxaline [22][23][24][25][26][27] groups are widely used in the synthesis of the D-A-D type polymers since z E-mail: mozkut@yyu.edu.tr; atilla.cihaner@atilim.edu.tr they have a strong electron withdrawing capacity, resulting in narrow bandgap polymers. It has been observed that quinoxaline-fused thiadiazoles have priority over single thiadiazole or quinoxaline groups based on their electron withdrawing capacity.…”
mentioning
confidence: 99%